Mitos Perkawinan dalam Sawér Pangantén: Analisis Semiotika Roland Barthes - Zannah, Putri Naufal Nurotul; Harini, Yostiani Noor Asmi; Durachman, Memen (Jurnal Bahasa dan Sastra, 2026)
Sawér Pangantén is a form of Sundanese oral literature that serves as a medium for advice and prayer in wedding ceremonies.  This study aims to reveal the denotative, connotative, and mythical meanings in Sawér Pangantén texts and the cultural values they contain. Previous studies have primarily emphasized the normative function of this tradition and have not positioned sawér as an ideological mechanism that shapes and normalizes social perceptions of marriage. This research employs a qualitative approach using textual analysis based on Roland Barthes’ semiotics. The data consist of a sixteen-stanza Sawér Pangantén text obtained through recorded oral narration from a native informant in Cisewu, Garut Regency, and subsequently transcribed verbatim. The analysis was conducted stanza by stanza by mapping the relationship between signifier and signified (denotation), cultural meaning (connotation), and second-order signification (myth) that naturalizes ideology. The findings reveal four axes of the myth of marriage: the social legitimation of husband-wife status, orientation toward well-being and harmonious prosperity, divine and ancestral legitimation, and an ethic of sacred caution articulated through prayer. At the level of myth, marriage is legitimized as a sacred institution aligned with divine will and accepted as a naturalized social order within Sundanese society.